Analisis OEE Mesin Kemasan Karton di UPT Provinsi Jawa Timur - Widyanti, Anggi Annastiti; Utomo, Yitno (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study evaluates the effectiveness of four main carton packaging production machines (slitter, slotter, die-cutter/pond, and board-to-board laminator) at a Provincial Technical Unit in East Java using Overall Equipment Effectiveness (OEE) within the Total Productive Maintenance framework. A quantitative descriptive approach was applied based on historical data from October 2025, including scheduled production time, downtime, output, defects, and ideal cycle time. OEE was calculated through Availability, Performance, and Quality components. The results show that average monthly OEE ranged from 18.75% to 32.39% when all days were considered, mainly due to several days with available time but zero output, which sharply reduced Performance and Quality. In contrast, on actual production days (output > 0), Availability remained high (94.52%–96.17%) and Quality was excellent (98.06%–100.00%). The die-cutter achieved an average OEE of 86.38%, meeting the world-class benchmark, while other machines ranged from 65.22% to 75.01%, indicating improvement opportunities in Performance.